Identification of Onosma visianii Roots Extract and Purified Shikonin Derivatives as Potential Acaricidal Agents against Tetranychus urticae - Sut, Stefania; Pavela, Roman; Kolarčik, Vladislav; Cappellacci, Loredana; Petrelli, Riccardo; Maggi, Filippo; Dall'Acqua, Stefano; Benelli, Giovanni (Molecules (Basel, Switzerland), 2017)
There is an increasing need for the discovery of reliable and eco-friendly pesticides and natural plant-derived products may play a crucial role as source of new active compounds. In this research, a lipophilic extract of Onosma visianii roots extract containing 12% of shikonin derivatives demonstrated significant toxicity and inhibition of oviposition against Tetranychus urticae mites. Extensive chromatographic separation allowed the isolation of 11 naphthoquinone derivatives that were identified by spectral techniques and were tested against Tetranychus urticae. All the isolated compounds presented effects against the considered mite and isobutylshikonin (1) and isovalerylshikonin (2) were the most active, being valuable model compounds for the study of new anti-mite agents.
Keywords: kořeny rostlin; Plant Roots; naftochinony; eco-friendly insecticide; akaricidy; Naphthoquinones; Tetranychus urticae; Animals; Plant Extracts; Tetranychidae; biopesticide; shikonin derivatives; Boraginaceae; rostlinné extrakty; zvířata; Acaricides; Onosma visianii